2010
DOI: 10.1007/s11095-010-0340-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Transition Metal Copper and the Ionophore A23187 in the Development of Irinophore C™

Abstract: Results explain why irinotecan loading rates are enhanced in the presence of formulations prepared with copper, and we speculate that the Irinophore C formulation exhibits improved drug retention, due to generation of a complex between copper and irinotecan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Previous studies suggested that drug retention can increase in formulations exhibiting higher drug‐to‐lipid ratios; an effect thought to be due to drug precipitation within the liposome core . For the loading method described here, however, it can be suggested that faster drug release rates would be associated with loss of the transmembrane pH gradient as well as loss of encapsulated copper which is known to complex topotecan and affect drug retention. Consequently, it can be suggested that increased internal copper levels and minimal dissipation of the pH gradient could result in improved drug retention.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggested that drug retention can increase in formulations exhibiting higher drug‐to‐lipid ratios; an effect thought to be due to drug precipitation within the liposome core . For the loading method described here, however, it can be suggested that faster drug release rates would be associated with loss of the transmembrane pH gradient as well as loss of encapsulated copper which is known to complex topotecan and affect drug retention. Consequently, it can be suggested that increased internal copper levels and minimal dissipation of the pH gradient could result in improved drug retention.…”
Section: Resultsmentioning
confidence: 99%
“…From previous reports, it is found that metal ions, such as Cu 2+ , Pt 2+ and Ce 4+ , can mediate effective loading of doxorubicin, topotecan and irinotecan, which is based on the complexation of drugs with metal ions. [7][8][9][10] Among them, we find that (i) Cu 2+ could mediate an effective and stable encapsulation of doxorubicin; 11 (ii) Cu 2+ may form a complex with Dox at a neutral pH and separate at an acidic pH, resulting in controlled release of Dox; 4,12 (iii) Cu 2+ has strong influences on the drug release rate, toxicity and efficacy. 11,13,14 Thus, the pH-sensitive CuDox precipitates within liposomes could retain the drug stability in circulation and reduce the toxicity; their application and development, however, are vastly limited due to slow release of the encapsulated drug.…”
Section: Introductionmentioning
confidence: 99%
“…IRI is entrapped in the acidic aqueous interior of the liposomes when a pH gradient is generated in the presence of the divalent metal ionophore A23187, which is required for the stability and maintenance of the pH gradient [21], [26]. The combination of the ionophore-generated pH gradient, together with the presence of encapsulated Cu 2+ , results in excellent drug retention properties for the formulation in vivo [26], [27], [28].…”
Section: Introductionmentioning
confidence: 99%